(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
The article discusses the use of Content and Language Integrated Learning (CLIL) technology, namely learning through integration of a foreign language with other subjects for students in non-philological areas. CLIL technology is used to motivate to learn a foreign language language and gives you the opportunity to apply your knowledge and skills in practice, is used to solve specific problems here and now. Also, the use of CLIL technology gives opportunity to develop communication and presentation skills